A rare case of chronic complete uterine inversion in a postmenopausal woman: a case report and literature review - Jie Hu; Weili Yang; Fang Zhang; Chunhong Yan (Journal of International Medical Research)
Uterine inversion is a rare condition that refers to the collapse of the fundus into the uterine cavity and occurs in puerperal and non-puerperal conditions. Non-puerperal uterine inversion is particularly infrequent. Diagnosing non-puerperal uterine inversion is often challenging because it resembles vaginal or cervical tumors and pelvic organ prolapse. Furthermore, this condition alters the anatomical structure of pelvic organs, thereby complicating diagnosis and treatment, and potentially leading to misdiagnosis with grave consequences. We report a case of a postmenopausal woman who presented with irregular vaginal bleeding and dysuria for 2 months. Preoperative enhanced pelvic magnetic resonance imaging suggested a benign tumor combined with uterine inversion, which was subsequently confirmed during surgery. A laparoscopic attempt to reposition the uterus failed, leading to successful repositioning via an abdominal incision and subsequent total abdominal hysterectomy with bilateral salpingo-oophorectomy. A histopathological examination showed a submucosal leiomyoma, which was smaller than that typically reported in other cases. We also conducted a review of previous cases to offer empirical guidance for the diagnosis and treatment of this rare condition.